2019
DOI: 10.3389/fcell.2019.00348
|View full text |Cite
|
Sign up to set email alerts
|

Know Thy Model: Charting Molecular Homology in Stromal Reprogramming Between Canine and Human Mammary Tumors

Abstract: Spontaneous canine simple mammary tumors (CMTs) are often viewed as models of human breast cancer. Cancer-associated stroma (CAS) is central for initiation and progression of human cancer, and is likely to play a key role in canine tumors as well. Until recently, however, canine CAS in general, and in CMT in particular, lacked detailed characterization and it remained unclear how canine and human CAS compare. This void in knowledge regarding canine CAS and the resulting lack of unbiased crossspecies analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 155 publications
(169 reference statements)
1
15
0
Order By: Relevance
“…It is well known that cellular migration involves integration into a complex microenvironment, which can be a physiological or pathological process, including regeneration tissues, immune response and tumor progression 12 , 36 40 , 56 – 58 . In addition to well-established chemotaxis, the microstructure and physical properties of the extracellular matrix have a significant influence on cell migration via durotaxis 12 , 56 – 58 . This process can be explained as a unidirectional cell migration mechanism in which a cell responds to an extracellular gradient of rigidity, which is important in the process of cell migration and invasion in tumour progression.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that cellular migration involves integration into a complex microenvironment, which can be a physiological or pathological process, including regeneration tissues, immune response and tumor progression 12 , 36 40 , 56 – 58 . In addition to well-established chemotaxis, the microstructure and physical properties of the extracellular matrix have a significant influence on cell migration via durotaxis 12 , 56 – 58 . This process can be explained as a unidirectional cell migration mechanism in which a cell responds to an extracellular gradient of rigidity, which is important in the process of cell migration and invasion in tumour progression.…”
Section: Resultsmentioning
confidence: 99%
“…Markkanen et al (94) analyzed CAS and normal stroma from 15 clinical cases using their laser capture microdissection (LCM) coupled with RNA-seq (LCMRNAseq) pipeline to identify stromal reprogramming in canine simple mammary carcinoma on a transcriptome-wide scale. They revealed strong increases in mesenchymal stem cells, gamma delta T-cells, macrophages, plasmoid dendritic cells, and natural killer T-cells in CAS and demonstrated that commonly deranged pathways between canine and human CAS included angiogenesis, epithelialmesenchymal transition, glycolysis, and immune response pathways.…”
Section: Genetic Heterogeneity and Epigenetics Of Tnbc And Cmtsmentioning
confidence: 99%
“…They showed that TGFbeta signaling, glycolysis, mitotic spindle, epithelial to mesenchymal transition, mTORC1 signaling, unfolded protein response, apical surface, interferon-gamma response and G2M checkpoint demonstrated greatly increased enrichment only in CAS and pathways involving pancreas beta cells, fatty acid metabolism, spermatogenesis, heme metabolism and IL2-STAT5 signaling showing dramatically reduced enrichment only in CAS. Markkanen et al (94) ranked the samples in The Cancer Genome Atlas (TCGA) breast cancer subset (that contains >1000 human tumor samples) analogous to the stromal enrichment scores to compare their canine-derived stromal signature and found that the canine-derived stromal signature was strongly positively associated with the enrichment of human-derived stromal signature of the TCGA breast cancer subset.…”
Section: Genetic Heterogeneity and Epigenetics Of Tnbc And Cmtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canine mammary tumors are an attractive model for translational oncology and might be useful for the evaluation of novel diagnostic and therapeutic applications, including immunotherapy [4,7,8]. Therefore, our objective was to investigate the expression of genes encoding different molecules related to T cell activity, such as co-stimulatory and co-inhibitory ligands that regulate T cell activation, transcription factors, chemokine receptors, and inflammatory cytokines in canine mammary tumors with different malignancy statuses and metastatic potential (benign, malignant, and metastatic).…”
Section: Introductionmentioning
confidence: 99%